Women rights crossing border and FGM/C: Violent traditions, cultural differences, and juridical conundrums - Falcão, R.; Carvalho, C. (Border crossings in and out of Europe, 2022)
In this article we look briefly into some of the conundrums around the practice of FGM/C. The practice, existent in dozens of countries, is often categorized as a “harmful traditional practice”, and a framework of “zero tolerance to FGM/C” has been created to combat it. We will describe how it became an agenda in the human rights framework, before we can discuss how the connections between Portugal and Guinea Bissau, have helped institutionalize an anti-FGM/C agenda in Portugal. We will also discuss the first condemnation for the practice of FGM/C in the country. This example will allow us to make some interpretations on how the juridical approach to the ban on this practice, despite seemingly consensual, is in reality contributing to new forms of invisibility (by pushing the practice underground), discrimination (association of certain groups to the practice) and double victimization (by punishing victims). We will also question the way policy is produced and intervention takes place.